Health Care Utilization and Payments of Postoperative and Drug Abuse-Related Spinal Infections. Issue 20 (15th October 2019) - Alhourani, Ahmad; Dietz, Nicholas; Sharma, Mayur; Ugiliweneza, Beatrice; Wang, Dengzhi; Nuño, Miriam; Drazin, Doniel; Boakye, Maxwell
Abstract : Study Design: Retrospective analysis of data extracted from the MarketScan database (2000–2016) using International Classification of Diseases (ICD)-9, ICD-10, and Current Procedural Terminology-4 codes. Objective: Evaluate the economic costs and health care utilization associated with spine infections. Summary of Background Data: Spinal infections ( SI) are associated with significant morbidity and mortality. A recent spike in SI is attributed to the drug abuse epidemic. Management of SI represents a large burden on the health care system. Methods: We assessed payments and outcomes at the index hospitalization, 1-, 3-, 6-, and 12-month follow up. Outcomes assessed included length of stay, complications, operation rates, and health care utilization. Outcomes were compared between cohorts with spinal infections: (1) with prior surgery, (2) drug abuse, and (3) without previous exposure to surgery or drug abuse, denoted as control. Results: We identified 43, 972 patients; 15.6% (N = 6847) of patients underwent prior surgery, 3.8% (N = 1, 668) were previously expose to drug abuse while 80.6% fell into the control group. Both the postsurgical and drug abuse groups longer hospital stay compared with the control cohort (5 d vs. 4 d, P < 0.0001). Exposure to IV drug abuse was associated with increased risk of complications compared with the control group (43% vs. 38%, P < 0.0001). Payments at 1-month follow-up were significantly ( P < 0.0001) higher among the postsurgical group compared with both groups. However, at 12-months follow-up, payments were significantly ( P < 0.0001) higher in the drug abuse group compared with both groups. Only postsurgical infections were associated with higher number of surgical interventions both at presentation and 1 year follow up. Conclusion: SI following surgery or IV drug abuse are associated with higher payments, complication rates, and longer hospital stays. Drug abuse related SI are associated with the highest complication rates, readmissions, and overall payments at 1 year of follow up despite the lower rate of surgical interventions. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textRetrospective analysis of MarketScan database comparing health care utilization of spinal infections (SI) following surgery and drug abuse with control cases. Drug abuse related SI showed the highest of complication rates, readmissions, and overall payments at 1 year of follow-up despite the lower rate of surgical interventions.